Perceived nervousness and moodiness associated with increased CVD but not cancer morbidity in pre- and postmenopausal women. Observations from the Population Study of Women in Gothenburg, Sweden - Hange, Dominique (Dove Medical Press, 2009)
A 32-year prospective observational study was initiated in 1968, including 1462 women aged 60, 54, 50, 46, and 38, representative of the female population in these age groups. Measures included self-reported nervous symptoms and moodiness at baseline, menopausal status, risk factors as smoking, s-cholesterol, s-triglycerides, body mass index (BMI), waist–hip ratio (WHR), blood pressure, and socioeconomic status (SES). The prevalence of nervousness and moodiness was investigated as well as if these reported symptoms could predict mortality and morbidity within 32 years in pre-and postmenopausal women. Women who reported at least two of the symptoms suffered from an increased risk of 32-year mortality, independent of all background variables described above (hazard ratio [HR] = 1.28, confidence interval [CI] 1.03–1.58). Women with only one of the nervous symptoms already had an increased risk of suffering from cardiovascular disease (CVD) also after multivariable adjustment (HR = 1.29, CI 1.09–1.52) a risk that also remained significant when analyzing CVD risk in the group of premenopausal women (HR = 1.28, CI 1.02–1.62). There was no significantly increased risk among pre-or postmenopausal women with perceived nervousness/moodiness of developing cancer during the 32-year follow-up. There seems to be an association between nervousness/ moodiness and premature mortality and morbidity in CVD, especially when present already in the premenopausal state in women.